Optimization and Modeling of Process Parameters on Bio-Char Yield of Low- and High-density Sawdust for Solid Fuel - Oluwasanmi Alonge; Olusola Oloruntoba; Temitayo Ogedengbe; Adedotun Adedoja; Imisioluwa Akintola (Journal of Renewable Energy and Environment)
Biochar has garnered significant attention as a potential substitute due to its favorable adaptability and equivalent metallurgical characteristics to coal and coke. An investigation was conducted to maximize the production of biochar with enhanced characteristics by carbonizing low-density (LDS) and high-density sawdust (HDS). The study utilized the Response Surface Methodology to predict the combined impact of processing factors, namely temperature, particle size, and residence time, on the yield of biochar. The aim was to identify the ideal circumstances that would result in an enhanced biochar yield. The optimum values for the HDS were numerically predicted as a temperature of 498.24°C, a residence time of 21.16 minutes, and a particle size mm. Under these conditions, the predicted fixed carbon yield was 57.40%, and the corresponding percentage yield was 25.54%. The optimum values for LDS were numerically predicted as a temperature of 474.70°C, a residence time of 25 minutes, and a particle size mm. Under these conditions, the predicted fixed carbon yield was 51.26%, and the corresponding percentage yield was 30.60%. The optimized biochar for the two types of sawdust exhibited improved energy contents (30 MJ/kg for HDS and 26.24 MJ/kg for LDS) and chemical elements comparable to coal, indicating that the biochar will be suitable for power generation. The study also concluded that temperature has the most significant effect on the quality of biochar produced from both HDS and LDS.